Pellet Embolus in Ulnar artery - A rare vascular Injury - Nine, SMA Zulker; Hossain, Mohammad Delwar; Hasan, AM Kamrul; Hasan, Md Kamrul; Khan, Nazmus Sakib; Mehar, Tahera; Ahmed, Niaz; Haider, Md Zulfiqur; Ahmed, Sohail (Pulse, 2022)
Intravascular embolization of bullets and other foreign bodies is a rare complication of penetrating trauma. It can represent a diagnostic challenge because it may present in various and unexpected ways. We report the case of a 65-year-old male who sustained shotgun pellet emboli to left ulnar artery following a right and left upper extremity gunshot injury. Pulse volumel.11 January-December 2018-2019 p.33-37